Engineering aspects of food biotechnology - Teixeira, José A. 1957-; Vicente, António A. (CRC Press, 2014)
Aimed at producing and improving food ingredients, developments in food biotechnology have focused on the fields of genetics and in enzyme- and cell-based biological processes. While the underlying science of these developments and applications has traditionally been well reported, there is a clear lack of information on the engineering aspects of such biotechnology-based food processes. This book provides a comprehensive review of these aspects, from the development of food processes and products to the most important unit operations.
Keywords: Food -- Biotechnology.; Bioengineering.; Biotechnology.; Engineering.; Food science.; elektronické knihy; electronic books